Maternal Reflections on Working from Home with Children during the Pandemic - Rosen, Lisa H.; Rubin, Linda J.; Beckmon Sharbine, Mackenzie (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
Due to widespread work and school closures during the early waves of the COVID-19 pandemic, many mothers were forced to work from home while supervising their children’s remote schooling. The current study examines maternal reflections on this period, focusing on the perceived impact of working in close proximity for both mothers and their children in the United States. Mothers reported that their children learned more about their job responsibilities since the onset of the pandemic compared to before it, which was likely due to children spending more time closer to their mothers while they worked. We used thematic analysis to examine mothers’ open-ended responses. Two overarching themes emerged. The first theme was that greater time together increases children’s understanding of working mothers’ role in the family, workplace, and community. The second theme was that observing one’s mother work from home can inform children’s future career paths. Mothers shared that this experience of learning about their mothers’ career enabled their children to better understand their perspective, which has the potential to be an empathy-building experience. Looking towards the future, this increased respect and empathy have the potential to improve relationship quality and help children view their mothers’ careers more favourably.